Penerapan Tanaman Obat Keluarga Di SMAN 2 Gorontalo - Mahmud, Agil Toriq; Nyare, Sahriah Alyantie; Datau, Husnina; Tangahu, Kelvin; Lauhi, Ahmad Gifary; Prasetia, Rezza Bagus; Pakaya, Randi; Biki, Rivaldi Kurniawan; Fauzan, Moh Nizar; Haryanni, Meri; Irawan, Safri (-, 2025)
The socialization and planting of Family Medicinal Plants (TOGA) at SMAN 2 Gorontalo aimed to enhance students' knowledge and skills regarding the use of medicinal plants as an alternative treatment and health maintenance. This activity was carried out over four days, including stages of location observation, obtaining permits, coordination meetings, and conducting socialization and practical planting of TOGA. Through an interactive approach, students were provided with understanding about various types of medicinal plants, their benefits, and how to plant and care for them. As a result, students not only gained theoretical knowledge but also practical skills that can be applied in daily life. The success of this activity demonstrates the importance of integrating nature-based education into the school curriculum, contributing to increased health awareness and environmental sustainability among students.